Empowerment of Nglongsor Village PKK Members in Utilizing Banana Peel Waste into Crackers: A Zero Waste Approach for Waste Management and Economic Improvement - Angga Setiawan; Cantika Miftahul Jannah; Yesita Inka Dela; Anisa Dwi Rofiah; Septia Dwi Alika Komarudin; Laili Aprilia Nurwakhidah (CV Media Inti Teknologi, 2026)
Background: Nglongsor Village has banana peel waste that has not been optimally utilized and causes environmental problems.Objective: Empowering PKK Mothers through training on processing banana peel waste into zero-waste crackers to support family economy.Methods: The activities were carried out through socialization, technical training, business assistance, packaging innovation, digital marketing, and evaluation, with 20 PKK members as participants.Result: Quantitatively, the program increased participants’ knowledge by approximately 70–80% based on pre-test and post-test results. A total of 18 out of 20 participants (90%) were able to independently produce banana peel crackers, contributing to an estimated 50% reduction in banana peel waste at the household level. In addition, one PKK business group was established with an average production capacity of 50 packages per production cycle.Conclusion: The program successfully reduced organic waste and enhanced women’s economic independence. These outcomes contribute to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 5 (Gender Equality), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production).